An Overview of Six Economic Zones in Nigeria : Challenges and Opportunities - World Bank (World Bank, Washington, DC, 2016)
This report provides a brief overview of six economic zones in Nigeria, and discusses the main findings with respect to the zones: development goals and the anticipated benefits of the zone projects, key implementation challenges and preliminary proposals on enhancing the development/implementation process moving forward. The objective is to improve the shared understanding of these six zone projects and to identify opportunities on how foreign investments in these six zones can provide the maximum possible benefits both for investing countries and the host country. Based on a preliminary assessment, it seems all six zones reviewed in this report have made some progress, albeit at different degrees. In terms of real development, the Lekki Free Zone and the Ogun-Guangdong Free Trade Zone have made the most significant progresses, with some on-site infrastructure already built or committed and several firms already operating in the zones. The zones in Abuja and Delta State are mostly in the early stages, but they seem to have strong government ownership and backing and each got several potential partners or anchor firms interested for investing.